Preparation and Characterization of Calcium-Chelated Sea Cucumber Ovum Hydrolysate and the Inhibitory Effect on α-Amylase - Xu Yan; Fengjiao Fan; Zijin Qin; Lijuan Zhang; Shuang Guan; Shiying Han; Xiufang Dong; Hui Chen; Zhe Xu; Tingting Li (Foods)
α-amylase can effectively inhibit the activity of digestive enzymes and alter nutrient absorption. The impact of ovum hydrolysates of sea cucumbers on α-amylase activity was investigated in this study. The protein hydrolysates generated using different proteases (pepsin, trypsin, and neutral protease) and molecular weights (less than 3000 and more than 3000) were investigated. The results showed that all three different hydrolysates demonstrated calcium-chelating activity and induced a fluorescence-quenching effect on α-amylase. The sea cucumber ovum hydrolysate with a molecular weight of less than 3000 Da, isolated using trypsin, showed the most effective inhibitory effect on α-amylase, with an inhibition rate of 53.9%, and the inhibition type was identified as mixed forms of inhibition. In conclusion, the generation and utilization of protein hydrolysates from sea cucumber ovum as a functional food ingredient could be a potential approach to add value to low-cost seafood by-products.